Study of dual Z-scheme photocatalytic response of TiO2/Ag/ZnO coating on plasma-modified cotton fabric for self-cleaning application - Zunaira Kashif; Muhammad Yasin Naz; Aiza Maqbool; Shazia Shukrullah; Muhammad Irfan; Salim Nasar Faraj Mursal; Saifur Rahman; Muawia Abdelkafi Magzoub Mohamed Ali (AIP Advances, 2024)
An innovative approach was adopted to improve the photocatalytic response of nanoparticle-coated cotton fabric for self-cleaning application. Fabrics with layers of TiO2, Ag, and ZnO nanoparticles were assessed for photodegradation of Rhodamine B, methyl orange, and methyl red. A dual-scheme charge transfer method was designed for the photocatalytic activity of TiO2/Ag/ZnO nanoparticles on cotton fabric. To produce the multilayer structure of nanoparticles, the fabric was first functionalized with atmospheric pressure nonthermal plasma and then sonochemically coated with TiO2/Ag/ZnO in a layered form. The plasma functionalization enhanced the stability of TiO2/Ag/ZnO nanoparticles on the fabric. It was revealed that a combination of Ag, TiO2, and ZnO nanoparticles produced a Schottky barrier among the silver metal and metal oxides (TiO2 and ZnO), resulting in enhanced photocatalytic properties. Methyl red underwent the highest photocatalytic degradation of 93% over the designed photocatalyst-coated fabric after 120 min of light exposure. This study provides a promising strategy for improving the photocatalytic self-cleaning efficacy of nanocoated fabrics.